Dynamics of phenotypic change: wing length declines in a resident farmland passerine despite survival advantage of longer wings. (2nd December 2016) - Dunn, Jenny C.; Hamer, Keith C.; Benton, Tim G.
Abstract : In many taxa, environmental changes that alter resource availability and energetics, such as climate change and land use change, are associated with changes in body size. We use wing length as a proxy for overall structural body size to examine a paradoxical trend of declining wing length within a Yellowhammer Emberiza citrinella population sampled over 21 years, in which it has been previously shown that longer wings are associated with higher survival rates. Higher temperatures during the previous winter (prior to the moult determining current wing length) explained 23% of wing length decrease within our population, but changes may also be correlated with non‐climatic environmental variation such as changes in farming mechanisms linked to food availability. We found no evidence for within‐individual wing length shrinkage with age, but our data suggested a progressive decline in the sizes of immature birds recruiting to the population. This trend was weaker, although not significantly so, among adults, suggesting that the decline in the sizes of recruits was offset by higher subsequent survival of larger birds post‐recruitment. These data suggest that ecological processes can contribute more than selection to observed phenotypic trends and highlight the importance of long‐term studies for providing longitudinal insights into population processes.